2010
DOI: 10.1073/pnas.1009778107
|View full text |Cite
|
Sign up to set email alerts
|

Two abundant proteasome subtypes that uniquely process some antigens presented by HLA class I molecules

Abstract: Most antigenic peptides presented by MHC class I molecules result from the degradation of intracellular proteins by the proteasome. In lymphoid tissues and cells exposed to IFNγ, the standard proteasome is replaced by the immunoproteasome, in which all of the standard catalytic subunits β1, β2, and β5 are replaced by their inducible counterparts β1i, β2i, and β5i, which have different cleavage specificities. The immunoproteasome thereby shapes the repertoire of antigenic peptides. The existence of additional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
277
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(289 citation statements)
references
References 39 publications
12
277
0
Order By: Relevance
“…To determine whether melanoma cells constitutively express IFN-inducible proteasome components and ERAP, seven cell lines were analyzed for the presence of PA28, ERAP1, β1i/LMP2, β2i/MECL-1, and β5i/LMP7. Immunoblot analysis revealed a strong expression of β5i/LMP7 and β1i/LMP2 in almost all cell lines suggesting the presence of mixed proteasome subtypes, as recently described [23]. Significant amounts of β2i/MECL-1 were detected in only one cell line, whereas PA28α/β and ERAP1 were broadly expressed even in the absence of IFN-γ (Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…To determine whether melanoma cells constitutively express IFN-inducible proteasome components and ERAP, seven cell lines were analyzed for the presence of PA28, ERAP1, β1i/LMP2, β2i/MECL-1, and β5i/LMP7. Immunoblot analysis revealed a strong expression of β5i/LMP7 and β1i/LMP2 in almost all cell lines suggesting the presence of mixed proteasome subtypes, as recently described [23]. Significant amounts of β2i/MECL-1 were detected in only one cell line, whereas PA28α/β and ERAP1 were broadly expressed even in the absence of IFN-γ (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Since β5i/LMP7 is abundantly expressed in melanoma cell lines, this setup might reflect the in vivo situation (Fig. 1A) [23]. In accordance with published results, we observed that β5i/LMP7-containing proteasomes mainly affected cleavage after V 35 thereby interfering with the C-terminal cut, and that β1i/LMP2-containing proteasomes also impaired the efficient production of the N-terminus.…”
Section: K G H G H S Y T T a E E A A G I G I L T V I L G V Lsupporting
confidence: 90%
See 2 more Smart Citations
“…Immune subunits and constitutive proteolytic subunits do incorporate into proteasomes together; in healthy organs, from onethird to half of all proteasomes are actually "mixed" proteasomes (for instance, containing catalytic subunits β1, β2, and β5i or β1i, β2, and β5i) (41). The existence of mixed proteasome subtypes is important for the generation of unique peptides for presentation by class I MHC and influences immune recognition (47,48). Moreover, β5i chaperone and proteolytic activity enhanced proteasome maturation and ensured optimal class I MHC expression (25), which is important for synaptic plasticity and refinement in the CNS (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%